Projeção da difusão de sistemas fotovoltaicos em consumidores residenciais de baixa tensão - Santos, Laura Lisiane Callai dos (2018)
Aiming at maximizing the potential growth of Distributed Generation for the residential market, the National Agency of Electrical Energy published the normative resolutions that establishes the general terms for connection of DG systems in distribution systems. Based on that, the consumers are allowed to play an active role in the power system by generating their own energy. On this matter, the solar photovoltaic generation (PV) is the most promising generation system for the low voltage consumers, especially for the residential sector, due to its easy installation. However, despite its potential benefits, photovoltaic generation may introduce uncertainties on distribution system planning studies, since the decision about connecting a PV system to the grid relies on the subjective judgement of each individual. Regarding that, this thesis presents a new methodology for projection of the diffusion of PV Systems in low voltage residential consumers considering two dimensions: throughout time and throughout space. It is considered that consumer’s decision in connecting a PV System to the grid is based on several aspects, which were classified in five groups: economical, management, political, social and technical. From that, there is the determination of barriers. From that, the system dynamics technique, combined with the Bass model, is applied to perform the projection of the diffusion of PV Systems throughout time. Then the projection throughout space is modeled. This methodology may be applied to strategic planning and to energy policies. In order to evaluate the performance and efficiency of the methodology, different scenarios of diffusion of PV systems are tested. Results demonstrate that the diffusion of PV systems depends on several factors such as the costs of PV panels, the energy tariff, incentives for adoption of PV systems (funding streams, incentive programs, service charges, microcredit, import taxes, interest rate policies and subsidies, feed-in tariffs, net metering and education campaigns) and the adoption by other consumers.